2019
DOI: 10.7554/elife.41723
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism gender differences in brain responsivity to emotional stimuli

Abstract: Men and women may use alcohol to regulate emotions differently, with corresponding differences in neural responses. We explored how the viewing of different types of emotionally salient stimuli impacted brain activity observed through functional magnetic resonance imaging (fMRI) from 42 long-term abstinent alcoholic (25 women) and 46 nonalcoholic (24 women) participants. Analyses revealed blunted brain responsivity in alcoholic compared to nonalcoholic groups, as well as gender differences in those activation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 76 publications
2
8
0
Order By: Relevance
“…AUD-related gender effects on brain structure also have been described, involving white matter volume [39][40][41][42], morphometry of the brain reward system [43], and cerebellar subregional volumes [44]. Additionally, we have reported AUD-related gender-dimorphic effects in multiple functional domains including emotional processing [45], personality [46], and drinking motives [5,47]. However, functional magnetic resonance imaging (fMRI) studies of AUD-related gender differences in the brain during performance of tasks involving emotion are rare [45].…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…AUD-related gender effects on brain structure also have been described, involving white matter volume [39][40][41][42], morphometry of the brain reward system [43], and cerebellar subregional volumes [44]. Additionally, we have reported AUD-related gender-dimorphic effects in multiple functional domains including emotional processing [45], personality [46], and drinking motives [5,47]. However, functional magnetic resonance imaging (fMRI) studies of AUD-related gender differences in the brain during performance of tasks involving emotion are rare [45].…”
Section: Introductionsupporting
confidence: 56%
“…Additionally, we have reported AUD-related gender-dimorphic effects in multiple functional domains including emotional processing [45], personality [46], and drinking motives [5,47]. However, functional magnetic resonance imaging (fMRI) studies of AUD-related gender differences in the brain during performance of tasks involving emotion are rare [45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not clear why despite the overlap between neural pathways underlying chronic pain and alcohol abuse, as well as the high comorbidity of both of those conditions with depression, the burden of depressive disorders is greater in people with ALC. Abnormalities in brain reward areas such as prefrontal cortex, anterior cingulate cortex, and insula, are consistently reported in association with chronic pain [18] and addictions [8,39]. Those same cortical regions are part of the depression neurocircuitry, but additionally, the ventral striatum, another reward system structure, has been reported to play a central role in depressive disorders [19].…”
Section: Discussionmentioning
confidence: 99%
“…Using software that provides automatic segmentation of hippocampal subfield volumes [6], three studies of abnormalities in AUD have reported smaller volumes of the subiculum, presubiculum, CA1, CA2+3, and CA4, or other parts of the hippocampus including dentate gyrus, hippocampal-amygdaloid transition area (HATA), and the fimbria [19][20][21]. In addition to brain abnormalities associated with AUD, interactions with age and gender have been revealed [22][23][24][25][26][27][28][29][30][31][32]. While the influence of age has been exemplified by a significant interaction of reduced volume of the CA2+3 region [19], hippocampal subfield projects in which women were included did not examine gender interactions [19,21].…”
Section: Introductionmentioning
confidence: 99%